Towards postcolonial management of transnational education - Ling, Peter; Mazzolini, M.; Giridharan, Beena (National Tertiary Education Union, 2014)
Increasingly universities in developed countries are engaging in transnational education. Responsibilities and opportunities to exercise management and leadership in the provision of transnational education depend on the organisational model adopted and whether the academics involved are on home or international campuses. Models range from neo-colonial control to transnational partnerships. In the Australian Office for Learning and Teaching study that informs this paper good practice in allocation and exercise of management and leadership responsibilities was identified and recommendations developed. A balance was struck between quality assurance obligations of the home institution, which imply a high level of home-based control, and the value of a degree of local control to the commitment of local academics involved, to their career opportunities, and to the educational experiences of their students.